Borrelia burgdorferi Population Dynamics and Prototype Gene Expression during Infection of Immunocompetent and Immunodeficient Mice - Hodzic, Emir (American Society for Microbiology, 2003)
The population dynamics of Borrelia burgdorferi were quantified by real-time PCR targeting the flaB gene in skin (inoculation site, noninoculation site, and ear), heart (heart base and ventricle), quadriceps muscle, and the tibiotarsal joint at 1, 2, 4, 6, and 8 weeks after intradermal inoculation in C3H and C3H-scid mice. In addition, RNA transcription was assessed for several prototype genes, including flaB, ospA, ospC, dbpA, arp, vlsE, fbp, oppA-2, and p37-42. Spirochete numbers were equivalent in C3H and C3H-scid mice at 1 or 2 weeks and then declined in C3H mice, but they continued to rise and then plateaued in C3H-scid mice. Gene transcription was likewise higher in C3H-scid mice than in C3H mice, particularly at 4 or more weeks of infection. Gene transcription showed variation among tissues, with the highest levels of transcription in heart and joint tissue, which are sites of inflammation.